2013
DOI: 10.1007/s12094-013-1028-y
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of annexin II expression in non-small cell lung cancer

Abstract: Annexin II was identified as a common prognostic factor in both LSC and AdC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Increased ANXA2 is correlated with poor prognosis of HCC patients. Previous research has shown that ANXA2 over-expression is correlated with poor prognosis of human gastric carcinoma [39], conventional renal cell carcinoma [40], nonsmall cell lung cancer [11,41], esophageal squamous cell carcinoma [42], urothelial carcinoma [43], multiple myeloma [44], and colorectal cancer [12] and predicts rapid recurrence after surgery of endometrial cancer [45] and in pancreatic cancer patients undergoing gemcitabine-adjuvant chemotherapy [46]. ANXA2 down-regulation is associated with recurrence and poor prognosis of prostate cancer [47] and oral squamous cell carcinoma [48].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased ANXA2 is correlated with poor prognosis of HCC patients. Previous research has shown that ANXA2 over-expression is correlated with poor prognosis of human gastric carcinoma [39], conventional renal cell carcinoma [40], nonsmall cell lung cancer [11,41], esophageal squamous cell carcinoma [42], urothelial carcinoma [43], multiple myeloma [44], and colorectal cancer [12] and predicts rapid recurrence after surgery of endometrial cancer [45] and in pancreatic cancer patients undergoing gemcitabine-adjuvant chemotherapy [46]. ANXA2 down-regulation is associated with recurrence and poor prognosis of prostate cancer [47] and oral squamous cell carcinoma [48].…”
Section: Discussionmentioning
confidence: 99%
“…ANXA2 staining score was the product of the intensity and percentage scores. The cutoff point for a statistically significant ANXA2 expression score in terms of survival was set using the X-tile software program and defined as follows: negative (−): (0-4), weakly positive (+): (4-6), moderately positive (++): (6-9), and strongly positive (9)(10)(11)(12). The staining in HCC and benign liver diseases tissues was scored independently by the two individuals who were blinded to each other's findings and the clinical characteristics of these sections (left panel, ×40, bar 500 μm; right panel, ×400, bar 50 μm) (χ 2 =46.305, P<0.001), single tumor node (χ 2 =7.707, P= 0.005), and early TNM stage (χ 2 =44.188, P<0.001), without intrahepatic metastasis (χ 2 =8.534, P=0.003) and portal vein tumor thrombus (χ 2 =19.988, P<0.001) had a significantly better prognosis (Fig.…”
Section: Univariate and Multivariate Analyses Of Prognostic Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulated evidence supported the pivotal role of Anxa2 in carcinogenesis and cancer progression [3,27,48,60]. Anxa2 overexpression has been observed in many human malignancy tumors, including breast cancer [41], colorectal cancer [8,10], pancreatic cancer [11,45], renal cell carcinoma [32], hepatocellular carcinoma [29,53], glioma [13], gastric cancer [9], and lung cancer [28]. The increased expression levels of Anxa2 in cancer tissues are associated with rapid recurrence [21,45], metastasis [32,52], poor response to chemotherapy [6,20], and poor prognosis [32,45].…”
Section: Introductionmentioning
confidence: 99%
“…Analogously, the elevated expression of annexin A2 was also detected in lymph node metastatic tissues of lung cancers. 12 In addition, annexin A2 also participates in vascular endothelial growth factor (VEGF)-mediated neovascularization. 13 It has been reported that several immunosuppressive cytokines, including VEGF are detected in the tumor microenvironment.…”
mentioning
confidence: 99%